2017
DOI: 10.1101/201228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of cross-orientation suppression and size tuning and the role of experience

Abstract: Many sensory neural circuits exhibit response normalization, which occurs when the response of a neuron to a combination of multiple stimuli is less than the sum of the responses to the individual stimuli presented alone. In the visual cortex, normalization takes the forms of cross-orientation suppression and surround suppression. At the onset of visual experience, visual circuits are partially developed and exhibit some mature features such as orientation selectivity, but it is unknown whether cross-orientati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Visual cortical neurons exhibit sublinear responses to the simultaneous presentation of two grating stimuli (Adelson and Movshon, 1982; Morrone et al, 1982; Morrone et al, 1987; DeAngelis et al, 1992; Heeger, 1992; Carandini et al, 1997; Simoncelli and Heeger, 1998; Reynolds and Heeger, 2009; Popovic et al, 2018), Because some of this suppression is likely present in the inputs to the cortex that arise from LGN (Freeman et al, 2002; Li et al, 2006; Priebe and Ferster, 2006), we designed an experiment to directly provide input to different regions of the cortical circuit itself, in order to separate cortical contributions to normalization from those of its inputs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual cortical neurons exhibit sublinear responses to the simultaneous presentation of two grating stimuli (Adelson and Movshon, 1982; Morrone et al, 1982; Morrone et al, 1987; DeAngelis et al, 1992; Heeger, 1992; Carandini et al, 1997; Simoncelli and Heeger, 1998; Reynolds and Heeger, 2009; Popovic et al, 2018), Because some of this suppression is likely present in the inputs to the cortex that arise from LGN (Freeman et al, 2002; Li et al, 2006; Priebe and Ferster, 2006), we designed an experiment to directly provide input to different regions of the cortical circuit itself, in order to separate cortical contributions to normalization from those of its inputs.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with a study that performed sparse stimulation of nearby orientation columns in tree shrew (Huang et al, 2014). One might have expected to find species differences between tree shrew and ferret because the tree shrew primarily exhibits length-summation in layer 2/3 (Chisum et al, 2003) while ferret exhibits both length-summation and surround suppression (Rubin et al, 2015; Popovic et al, 2018), but both species showed non-specific spread of activity in layer 2/3.…”
Section: Discussionmentioning
confidence: 99%
“…In order to examine the initial state of spatiotemporal receptive fields (Figure 1) and to understand how these fields are altered during the short critical period for the emergence of direction selectivity, we carried out in vivo intracellular recordings in the visual cortex of anesthetized ferrets using sharp microelectrodes. Intracellular recordings were used because naïve visual cortical neurons exhibit lower firing rates than experienced animals (Clemens et al, 2012;Popovic et al, 2018), and we wanted to be able to examine the receptive field properties of the subthreshold voltage in addition to spiking. Experimental animals were split in to 2 age groups: visually naïve ("naïve": age P30-34, n = 10 animals, 23 cells) and visually experienced ("experienced": age P40-60, n = 11 animals, 29 cells).…”
Section: Resultsmentioning
confidence: 99%
“…Visual stimuli: Visual stimuli were created in MATLAB with the Psychophysics Toolbox (Brainard, 1997;Pelli, 1997;Kleiner et al, 2007) on a Macintosh Pro running OSX and displayed on a Dell monitor 1704FPVt (40 cm viewing distance). Gratings were shown in pseudorandom order at temporal frequencies that varied between 2 -8 Hz and a spatial frequency of 0.08 cycles per degree, which is in the middle of the maximal response functions for animals in this age range (Li et al, 2006;Popovic et al, 2018). Sparse noise stimuli for reverse correlation analysis were 1-dimensional bar stimuli, rotated so that the bar orientation matched the preferred orientation of each cell (Priebe and Ferster, 2005;Rust et al, 2005).…”
Section: Sex As a Variablementioning
confidence: 99%